The Rate of Interest, the Bank Rate, and the Stabilization of Prices - Cassel, Gustav (Quarterly Journal of Economics, 1928)
Relative prices and the absolute height of prices. — Interest as a price, 512. — The equilibrium rate of interest is a price; how it is determined, 513. — The absolute height of prices, 515. — The bank rate, 516. — Stability of prices is possible only when the bank rate is the same as the equilibrium rate, 517. — No other device is adequate, 519. — The gold standard does not bring stability of prices, 520. — A manipulated bank rate may mitigate the instability, but with disturbing effects, 521. — Some explanations: special conditions of a progressive society; various kinds of interest rates; how the rate of interest affects prices, 523. — Dynamic as contrasted to static conditions; cyclical movements; futility of mathematical wave theories, 526.